Effects of phosphorus in the wastewater from intensive catfish farming ponds on the growth and phosphorus uptake of Hymenachne acutigluma (Stued.) - Kieu, Le Diem; Nguyen, Pham Quoc; Nguyen, Pham Quoc; Tuoi, Tran Thi; Tuoi, Tran Thi; Trang, Ngo Thuy Diem; Trang, Ngo Thuy Diem (Academia Journal of Biology, 2019)
Hymenachne aquatic grass, Hymenachne acutigluma was planted in the wastewater from intensive striped catfish (Pangasianodon hypophthalmus) cultivating ponds containing 2.1 mg N/L, which was enriched with a serious of inorganic phosphorus concentrations. The experiment was arranged in a completely randomized design with three replications in the net house for 42 days. The results showed that P concentrations did not significantly affect the growth of Hymenachne. The presence of high P concentrations resulted in the increase of P content in plant tissues leading to higher phosphorus absorption at the P levels of 8 and 10 mg P/L. H. acutigluma removed 12.1–27.6% P from 88.3–95.9% P in the wastewater of striped catfish pond. This result indicated the low concentrations of N (2.1 mg N/L) and of 1–10 mg P/L were not optimal for the growth of H. acutigluma. Hymenachne acutigluma, intensive striped catfish, wastewater, phosphorus, biomass, nutrient uptake.